Spatial effect in the efficient access of rural development - Erniel B. Barrios (Asian Development Bank Institute (ADBI), 2007)
The search for an effective policy direction to contribute to the alleviation of rural poverty requires understanding of various socio-economic dynamics affecting the household. The central issue in the economic dimension is inefficiency in production, which may contribute to the widening income gap among rural households. Spatial externalities are introduced into a stochastic frontier model in the analysis of rural households' efficiency in utilizing various factors of production including development interventions (infrastructure and capability-building activities) and other localized endowments. Output is measured in terms of income and perceptions on various aspects of rural development summarized into an index. Provision of rural roads and other rural infrastructure should be bundled properly with support services and capacity building activities. This can enhance the demand for other infrastructure and services resulting in a dynamic evolution of essential elements in the pursuit of rural development. Bundles of intervention improve production efficiency of rural households at the different stages of production in-farm and/or off-farm. Spatial indicators illustrate the role of geographical dynamics (physical, social and cultural factors) in rural development, justifying a site-specific, participatory approach in development intervention. Although site-specific interventions may be costly at first, they become more efficient in the long-run. Benefits from an intervention in one community are expected to produce ripple effects that reach its spatial neighbors. Stakeholders' contribution in maintenance is feasible provided that there is a true sense of ownership of the infrastructure/project, usually evolving through a participatory approach. Public investment in infrastructure and user's fees can complement one another; continuous provision of new infrastructure and maintenance of existing infrastructure can add up to a sustainable track towards rural development. A socialized user's fee system can be used as a vehicle to prevent the potential widening of income disparity in rural areas. It is important however to carefully choose a suitable and acceptable basis for the socialized user's fee rates. An incorrect choice can be perceived as a disincentive for access or might stimulate distrust among the affluent segment of the rural society regarding the sincerity of the government in pushing rural development. An unsuitable basis for user's fee rates could thus eventually lead to more social problems instead of bridging inequality.
Keywords: 330; rural development; rural infrastructure; household efficiency; spatial autoregression; spatial stochastic frontier; Ländliche Entwicklung; Ländliche Infrastruktur; Technische Effizienz; Privater Haushalt; Autokorrelation; Schätzung; Philippinen